2020
DOI: 10.15252/embj.2020105594
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 infection of CD4 T cells impairs antigen‐specific B cell function

Abstract: Failures to produce neutralizing antibodies upon HIV‐1 infection result in part from B‐cell dysfunction due to unspecific B‐cell activation. How HIV‐1 affects antigen‐specific B‐cell functions remains elusive. Using an adoptive transfer mouse model and ex vivo HIV infection of human tonsil tissue, we found that expression of the HIV‐1 pathogenesis factor NEF in CD4 T cells undermines their helper function and impairs cognate B‐cell functions including mounting of efficient specific IgG responses. NEF interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…Mock inoculated BLTS-humanized mice (n=4) were used for controls, with those mice showing no detectable HIV genome (C; timepoints data not shown). Not significant (ns) = P>0.05, * = P≤ 0.05, ** = P≤ 0.01, *** = P≤ 0.001, **** = P≤ 0.0001. tissue culture studies demonstrate that Nef promotes B cell dysregulation via impairment of CD4+ T cell-B cell interactions (Kaw et al, 2020). We demonstrated that Nef homodimerization is crucial for Nef-mediated enhancement of HIV infectivity and replication as well as dysregulation of host defenses in tissue culture models (Li et al, 2020;Poe and Smithgall, 2009;Rosa et al, 2015;Ryan P. Staudt, 2020;Trible et al, 2006a).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Mock inoculated BLTS-humanized mice (n=4) were used for controls, with those mice showing no detectable HIV genome (C; timepoints data not shown). Not significant (ns) = P>0.05, * = P≤ 0.05, ** = P≤ 0.01, *** = P≤ 0.001, **** = P≤ 0.0001. tissue culture studies demonstrate that Nef promotes B cell dysregulation via impairment of CD4+ T cell-B cell interactions (Kaw et al, 2020). We demonstrated that Nef homodimerization is crucial for Nef-mediated enhancement of HIV infectivity and replication as well as dysregulation of host defenses in tissue culture models (Li et al, 2020;Poe and Smithgall, 2009;Rosa et al, 2015;Ryan P. Staudt, 2020;Trible et al, 2006a).…”
Section: Introductionmentioning
confidence: 75%
“…Previous studies also show that HIV Nef dimers are required to activate non-receptor tyrosine kinases of the Src and Tec families to enhance viral replication (Staudt et al JBC 2020) and are also linked to downregulation of MHC-I and CD4 receptor on T cells (Poe and Smithgall, 2009; Shu et al, 2017). Additionally, Nef promotes B cell hyper-activation and dysregulation; this pathogenic effect has been associated with T cell interaction (Chirmule et al, 1994; Kaw et al, 2020). Dysregulated immune activation and signaling by Nef are presumed to drive chronic HIV infection and progression to AIDS (Lori, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaw et al (2020) discovered such a mechanism and describe it in an elegant new study published in this issue of the EMBO Journal. They found that the HIV‐1 pathogenesis factor NEF, a small virus‐encoded myristoylated protein of 27–36 kDa, which is expressed at high levels throughout the viral replication cycle, prevents proper T‐cell help to B cells, resulting in reduced GC formation, prevention of B‐cell expansion, and inhibition of somatic hypermutation.…”
Section: Figure Expression Of Hiv‐1 Protein Nef In Cd4 T Cells Leads mentioning
confidence: 98%